Composite fractional-order sliding mode controller for PMSM drives based on GPIO. (November 2022) - Ge, Haoran; Liu, Yijian
In order to optimize the performance of permanent magnet synchronous motor (PMSM) drives, a fractional-order sliding mode (FOSM) control scheme combining generalized proportional integral observer (GPIO) is adopted in this paper. A FOSM controller is firstly employed to reduce the negative effects of the load torque and parameter variations in the PMSM system. However, the FOSM control method mostly needs high control gain to moderate the unfavorable effects of the total disturbance, which will inevitably lead to large chattering phenomenon. Therefore, the unknown lumped disturbance is effectively estimated by using a GPIO, and the estimated value is synchronously compensated to the FOSM speed controller. Even if a smaller control gain is chosen, the robustness of the proposed composite GPIO-based FOSM controller is better than that of the FOSM controller. Finally, the effectiveness of the proposed control strategy is verified by comprehensive simulation and experimental results.